Study on Sedation with Local Analgesia in Calves - Sarker, NC; Hashim, MA; Ray, BP; Sarker, SK (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. The effect of sedatives and analgesics on heart rate, respiration rate and rectal temperature were observed. Heart rate and respiration rate significantly decreased during sedation with xylazine hydrochloride plus 2% lignocaine hydrochloride or 0.5% bupivacaine hydrochloride. A significantly decreased heart rate and respiration rate also found during sedation with diazepam plus 2% lignocaine hydrochloride or 0.5% bupivacaine hydrochloride. Two percent lignocaine hydrochloride showed short onset, rapid spreading and no side effect. Duration of analgesia was longer with 0.5 % bupivacaine hydrochloride (55.88±1.58 min in Group B and 48±11.25 min in Group D) compared to 2% lignocaine hydrochloride (39.60±5.77 min in Group A and 43.6±5.81 min in Group C). Xylazine hydrochloride showed short onset and long duration of sedation compared to diazepam. So for herniorraphy, xylazine hydrochloride can be used as a better sedative while 0.5 % bupivacaine hydrochloride can be used as a local analgesic for longer duration of action.Key Words: lignocaine hydrochloride, sedation, analgesiaNC Sarker et al/Animal Production 13(3):191-197 (2011)